As múltiplas dimensões do fazer pedagógico criativo de uma escola alagoana: contribuições no sentido da construção de um ambiente inclusivo - Pereira Filho, Adalberto Duarte (2019)
This research investigated the contributions of creative pedagogical practices to school inclusion. It had as a general objective to highlight the creative movements of the school for the construction of an inclusive environment. Specifically, this study aimed to: (a) understand the contributions of complexity, transdisciplinarity and ecoformation for the construction of creative schools; (b) identify the multiple dimensions of the school in which creativity needs to be mobilized in order to build an inclusive school environment; (c) to analyze how these multiple dimensions, through which creativity manifests, contribute to the construction of an inclusive environment. To meet these objectives, a qualitative-quantitative methodological design was drawn. Due to the singularities of the pedagogical practices developed, the Sun and Moon School was taken as the research scenario and as subjects of the research, the teachers who worked in it. In this sense, the study was configured as a single case study type. The multiple dimensions through which creativity is mobilized to make this institution an inclusive environment have been verified from the Instrument for Valuing the Development of Educational Institutions (VADECRIE). The application of this instrument took place in person and in printed form. Ethical care has been taken. The research project was submitted to the Research Ethics Committee of the Federal University of Alagoas (CEP / UFAL) and in response we received its approval through opinion nº 3,183.06. The Colégio Sol e Lua has a faculty composed of 19 teachers, of whom 15 have agreed to participate in this research, responding to VADECRIE. This instrument is composed of 10 categories and each category comprises 10 questions. Each question should be answered on a scale of 1 (one) to 10 (ten). 1 (one) means the lowest level of creativity and 10 (ten) the highest level. All 100 questions were answered by these 15 subjects and with that returned 1500 responses with different degrees of measurement for the indicators of creativity listed in VADECRIE. This volume of data was organized into frequency tables and pie charts. The analytical treatment was based on the measures of central tendency of the descriptive statistic, more specifically the fashion. In addition to the statistical analysis, the references of complexity, transdisciplinarity and ecoformation, which were the basis of this research, shed light on these numerical data and allowed us to see beyond the information that the fashions of the responses to the VADECRIE indicators allowed us. As a result of these analyzes it was possible to verify from the data measured by the teachers of the Sun and Moon School that this school demonstrated creative movements towards the construction of an inclusive environment. This data can be verified from the percentage of the answers of the professionals who are in the front line of the pedagogic doing. Statistically, the indicators of creativity of this school indicated their concern with the inclusion of the subjects. The complex, transdisciplinary and ecoforming look present in this institution, from the pedagogical proposal to the educational practices, contributed greatly to the manifestation of these results. However, even in the face of these results, it is imperative that institutions that seek, through creativity, the constitution of inclusive spaces, never lose sight of the need to value individually the human dimensions of the human.